CARA ASYIK DAN CEPAT MENYELESAIKAN SOAL-SOAL MATEMATIKA - Simamora, Yumira; Lubis, Ulfa Annisa; Rafidah, Rafidah (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2024)
Mathematics is often considered a difficult and scary subject for students, thereby reducing their motivation and understanding in solving mathematics problems. This research aims to introduce a fun and fast learning method for solving mathematics problems through a systematic and interactive problem solving strategy approach. This activity was carried out in the form of community service at SMKS Telkom 1 Medan using demonstration and direct practice methods. The results of the activity showed an increase in students' understanding and motivation towards mathematics, especially in using tricks to solve problems in a faster and more efficient way. Evaluation through pre-test and post-test shows that students have experienced significant improvements in solving questions more precisely and confidently. Thus, the use of innovative and fun learning methods can help students overcome difficulties in learning mathematics and improve their problem solving skills.